PENDIDIKAN ISLAM DI THAILAND - Yuliani Yuliani; Edy Purwanto (EDUCATIONAL JOURNAL : General and Specific Research, 2022)
Islam in Thailand is a minority religion. The development is not as fast as in other Asian countries. It gets attention because the spread of Islam in Thailand was brought by Muslim figures through trade routes coming from the Arab region and the coast of India, Through the Samudra Pasai Kingdom in Aceh, Ethnic Chinese, Ethnic Champa and Ethnic South Asian. As evidence there are Islamic relics in Thailand Is a tombstone inscribed with Arabic, Java Mosque, Canals and water systems in Krung Theyp Mahankhon, Islamic books in Arabic Jawi, Ancient painting and the famous Sufi scholar. Education promoted by the Thai royal government Classified as discriminatory against Islam and minorities Due to the lack of people who are Muslim. Problems faced by Thai Muslims Is a minority group problem who must coexist peacefully with non-Muslims In the same country. They are in a Dilemma How to do reconciliation among the fundamental Islamic beliefs With the need to be a good citizens In a country dominated by a non-Muslim population.